Dynamic analysis of fluid–structure interaction problems with modal methods using pressure-based fluid finite elements - Sigrist, Jean-François; Garreau, Stéphane (Finite elements in analysis and design, 2007)
The present paper deals with numerical developments performed in the finite element code ANSYS in order to produce coupled fluid–structure dynamic analysis with pressure-based formulation, using modal and spectral methods. Enhancement of the modelling possibilities within the ANSYS code is carried out with implementation of fluid–structure symmetric formulations for elasto-acoustic and hydro-elastic problems, using the so-called symmetric ( u , p , ϕ ) and ( u , η , ϕ ) formulations. Using symmetric formulation enables linear dynamic analysis with modal projection techniques for a fluid–structure coupled system. The paper briefly recalls the basic principles of such methods in the context of FSI. Validation of the developments performed in the ANSYS code is exposed, focusing in particular on the calculation of effective mass for coupled eigenmodes. Industrial application is also presented and gives a validation test case for modal and spectral methods with FSI modelling.